How green was by valley. - Llewellyn, Richard ([Place of publication not identified] : Macmillan, 1940)
Tells of the Morgans, a Welsh family of miners and the valley in which they live, a valley doomed to destruction by the encroaching slag heap.
Keywords: Coal mines and mining -- Fiction; Wales -- Fiction